Analysis of Impact of the Different Node Architectures and Wavelength Channel Protection on the Availability WDM Ring Networks - Rados, Ivan; Schwartz, Ladislav (Communications - Scientific letters of the University of Zilina, 2009)
This paper investigates the availability of WDM (Wavelength Division Multiplying) ring networks. An analysis of different nodes, composed of passive and active components, is then carried out, as well as their availability. The availability for optical link, and especially the Span Protection and Route Diversity, is analysed as well. The wavelength channel protection principles being used in WDM ring networks are particularly explicated: OCh (Optical Channel) dedicated and OCh shared protection. The availability models for a WDM ring using these types of protection are given as well as the impact of availability for nodes and optical links on the entire ring availability. Data on the intensity of failures and mean time to repair are taken from different literature.